Letter (copy) : International conference, 10-11 March 1937 - Bell, Ernest A.
021-0047-001 EAB/514 International. 6th March 1937. Mr. - Knappett, Co-operative Printing Society, Tudor Street, LONDON. E.C. Dear Mr. Knappett, INTERNATIONAL CONFERENCE 10-11 MARCH, 1937. Will you please be good enough to print 100 copies of a card identical with the enclosed copy. The colour of the card should match as nearly as possible. If you could let us have these cards by Tuesday morning, we would be obliged. Yours sincerely, International Department. Copy. Admission Card 292/946/21/47